Spin-2 operators in two-dimensional N $$ \mathcal{N} $$ = (4, 0) quivers from massive type IIA - Shuo Zhang (Journal of High Energy Physics)
Abstract In this work we revisit the problem of studying spin-2 fluctuations around a class of solutions in massive type IIA that is given by a warped AdS3 × S2 × T4 × I ρ $$ {\mathcal{I}}_{ρ } $$ and with N $$ \mathcal{N} $$ = (4, 0) supersymmetry. We were able to identify a class of fluctuations, which is known as the “minimal universal class” that is independent of the background data and saturates the bound on the mass related to the field theory unitarity bound. These operators have conformal dimension ∆ = 2(ℓ + 1), with ℓ being the quantum number of the angular momentum on the S2. We also computed the normalisation of the 2-point function of stress-energy tensors from the effective 3-dimensional graviton action. We comment on the relation of our results to the related AdS3 and AdS2 solutions in massive type IIA and type IIB theories respectively.